Coefficient of restitution of kiwifruit without external interference. (August 2022) - Wu, Zhenchao; Li, Guo; Yang, Ruizhe; Fu, Longsheng; Li, Rui; Wang, Shaojin
Abstract: Coefficient of restitution (CoR) is an important parameter required to simulate kinematics and collision physics of various materials using simulation software. Most current methods for determining the CoR of fruit-fruit collision (FFC) may be interfered by other colliding objects. In this study, a platform was designed to realize the FFC of kiwifruit without introducing other colliding objects, where influences of different factors (including ripening time, collision velocity, and fruit collision posture) on the CoR were studied. Total bruise volume (TBV), the sum of two fruit bruise volumes after the FFC, was measured and correlated with the CoR. Results showed that the CoR on early ripening time was large and its standard deviation was small, but opposite on late ripening time. The CoR of the FFC decreased with collision velocity increasing, except for the late ripening time. The fruit collision posture had also affect on the CoR because the difference in the rotation angle of the fruit during the FFC. Moreover, the TBV decreased with increasing of the CoR and was 0 mm 3 when the CoR exceeded 0.58. The CoR could not only be an appropriate parameter to predict fruit damage and describe bruise initiation, but also be used for simulations on the early ripening time. This research will help establish a more accurate fruit model and thus designing optimal fruit post-harvesting and processing systems. Highlights: A platform was designed to realize fruit collision without external interference. CoR was deduced using a velocities-function derived based on fruit deformation. CoR decreased with collision velocity increasing at the same ripening time. The CoR could be an appropriate parameter for fruit damage prediction.